Obligation and Free Will: A Philosophical Study - Gayen, Bhabesh (Department of Public Administration, 2024)
Every person wants to keep the society healthy and for keeping the society healthy, various rules and regulations are necessary. But when the disciplinarian becomes a consumer rather than a protector, then people need freedom. They want to create a healthy society through free choice. Philosopher Jean Paul Sartre said in his existential philosophy about freedom that there are two types of being, being-in-itself and being-for-itself. Where being-in-itself is an entity that has no free choice, that cannot voluntarily change. Such as brick, wood, sand, stone etc. entities cannot change by themselves. But he admits another kind of being, which is being-for-itself or human being. By the free choice of human being can change themselves. By their free choice they can avoid immoral acts and does moral acts. One can choose what is universally good by avoiding what is universally evil. As a result of which a universally peaceful society can be developed. But the crucial question is whether people can choose freely? Have people choice anything freely? We observe that the freedom of one man in society is always limited to the tip of another man's nose. That is, people are bound by various chains as economic, social, political, religious, legal, etc. That is, he must choose within the limits. So, can people be truly free? Or can people be truly free to choose something? But in Sartre's existential philosophy, we notice that people are free by nature. That is, people always make free choices in one way or another or people must make some kind of independent choice every moment. For example, when my mother asks me to eat something, if I obey my mother and eat the food, then it is my own choice, and even if I do not take the food because I am not so hungry, it is also my free choice. That is, people make independent choices in every case or they must make independent choices. That is why he says that people are condemned to freedom. That is, people are forced to choose freely here. But the question: if people are forced to make free choices, is it real freedom? Such issues will be discussed critically in the said article. Again, an attempt will be made to assess such problems through Kant's concept of morality.